BUILDING A MULTIMEDIA-BASED MULTIPRESENTA BUSINESS: STRATEGIES TO UNLOCK OPPORTUNITIES FOR DIGITAL CREATIVITY - Eliagus Telaumbanua; Siska Putri C. Lase; Lenta Iman S. Lase; Seven D. Zai; Yobi Hura; Jefriniat J. Zendrato (JOURNAL OF COMMUNITY DEDICATION, 2025)
The community service program in Hilimoasia Dua Village aims to improve the understanding and skills of Micro, Small, and Medium Enterprises (MSMEs) in multimedia-based multi-presentation businesses. Through training and mentoring, participants experienced a significant increase in the understanding of multimedia concepts and their application in business. Before participating in the program, many MSMEs had limited knowledge about multimedia, but after training, they were able to understand the potential of multimedia to increase competitiveness. In addition, the skills in creating engaging multimedia content, such as promotional videos and interactive presentations, are also improved, providing added value to their efforts. The program also emphasizes the importance of digital marketing, where participants are taught to leverage social media platforms, websites, and email marketing to reach a wider market. Data analysis in digital marketing is in focus, allowing MSMEs to understand consumer behavior and adjust strategies in real-time. In addition, collaboration between MSME actors is strengthened through the network built during the program, creating profitable synergies. Program evaluations show that the majority of participants feel satisfied and willing to recommend the program to others. While there are variations in assessments on some aspects, overall, the program has succeeded in improving the skills, understanding, and network of business actors, which are key to business success in the digital age. This program is expected to be a model for the development of MSMEs in other regions.